LGBTQs and LAW’S Violence Within a Heteronormative Landscape - Donnelly-Drummond, Anthony (Frontiers in Sociology, 2021)
This article raises concerns as to the way in which specific exemptions within equality law across the United Kingdom may be viewed as a form of violence against LGBTQs.1 The overarching concept of heteronormativity and its impact is aired. The possible impact of exemptions for religious organisations to legally discriminate on grounds of sexual orientation under Northern Ireland’s Equality Act 2006 acting as a catalyst for the Asher’s cake incident, is reviewed. Similarly, the effect of exemptions under the Equality Act 2010 feasibly lending support for protestors against inclusion of LGBTQ issues in a Birmingham school is made clear. Thereafter the invisibility of LGBTQs within curricula is raised alongside the legacy of section 28. Overall, the article raises the spectre that specific aspects of equality legislation, designed to protect individuals on a range of grounds, may be perceived as not only flawed but inherently violent due to the dehumanizing impact on LGBTQ people. In addition, concerns are raised that against this background, within the United Kingdom there has been a failure to educate all students as to contemporary issues of diversity, potentially harming their development as citizens in our diverse contemporary society.